Breast MRI Teaching Atlas - Ha, Richard; Comstock, Christopher E.; Morris, Elizabeth A. (Springer New York : Imprint: Springer, 2017)
This atlas serves as a basic introduction to breast MRI. Organized by case, it emphasizes pertinent breast MRI findings and common indications for breast MRI. Topics include breast MRI basics, benign findings, breast malignancy, high-risk conditions, interesting cases, and breast implants. Brief teaching points accompany each case and highlight the importance of the findings. Breast MRI Teaching Atlas is an ideal resource for diagnostic radiologists, residents, fellows, and clinicians involved in the care of breast cancer patients, including surgeons, oncologists, and obstetricians/gynecologists. - Resumé vydavatel
Keywords: rakovina prsu; nukleární magnetická rezonance; nemoci prsu; radiologie; breast cancer; nuclear magnetic resonance; breast diseases; radiology; elektronické knihy; atlasy; electronic books; atlases